Bleeding edge [a novel] - Pynchon, Thomas 1937- (Penguin, 2013)
New York City, 2001. Fraud investigator Maxine Tarnow starts looking into the finances of a computer-security firm and its billionaire geek CEO and discovers there's no shortage of swindlers looking to grab a piece of what's left of the tech bubble
Keywords: Women private investigators / Fiction; High technology / Fiction; Swindlers and swindling / Fiction; Murder / Investigation / Fiction; New York (N.Y.) / Fiction; Fiktionale Darstellung